Nitrogen, Sulphur and Thiourea Nutrition of Pearl millet [Pennisetum glaucum (L.) R. Br.] II. Effect on Yield and Yield Components - Parihar, G N; Sahu, M P; Joshi, N L (Annals of Arid Zone, 2016)
Response of pearl millet to nitrogen. sulphur, and seed and foliar application of thiourea, a sulphydryl compound. was studied under arid conditions for three consecutive seasons. Application of 40. 80 and 120 kg N ha-1 significantly increased mean grain yield by 46.7. 72.1 and 71.7% and stover yield by 16.9. 33.1 and 38.9%. respectively. Increase in yield due to N was a cumulative effect of significant increases in yield attributes (number of ears plant-1 by 7.2-9.9%. number of grains ear-1 by 11.0-27.2%. 1000-grain weight by 12.5-18.4%). Sulphur application had no significant effect on grain yield, even though the available sulphur content of the soil ranged between 8.4 to 8.9 ppm. The N:S ratio of leaves remained around 14. indicating. presence of efficient mechanism for sulphur uptake and translocation’ by the crop. Pearl millet was thus identified as S-efficient crop. Foliar spray of 1000 ppm thiourea significantly increased yield attributes especially the lOOO-grain weight. Dry matter distribution either in leaves or stems decreased due to thiourea spray and there was commensurate increase in dry matter distribution in ears leading to enhancement in capacity of developing grains to accept carbohydrates and consequent increase in yield by 0.181 t ha-1 over untreated control. Thiourea seed plus foliar treatment led to further improvement in grain yield.